Working on professional development of faculty staff in higher education: investigating the relationship between social informal learning activities and employability. Issue 2 (14th March 2016) - Gerken, Maike; Beausaert, Simon; Segers, Mien
Abstract : In this study, we examined how social informal learning and formal learning of faculty staff in higher education relate to their employability. Data were collected from 209 faculty staff members working at a Dutch university. Results showed that social informal learning was related to the employability of faculty staff. Further analysis revealed that especially external information seeking and acting upon feedback from colleagues and not formal learning predicted the employability of faculty staff. The finding suggests that institutes of higher education should especially foster the professional development of their faculty staff by stimulating exchange of information and seeking and using feedback with colleagues in a proactive manner.